Burden of opioid use for pain management among adult herpes zoster patients in the US and the potential impact of vaccination. Issue 5 (30th November 2022) - Poirrier, Jean-Etienne; DeMartino, Jessica K.; Nagar, Saurabh; Carrico, Justin; Hicks, Katherine; Meyers, Juliana; Stoddard, Jeffrey
ABSTRACT: The goal of this research was to describe treatment patterns, health-care resource utilization, and costs for herpes zoster (HZ)-related pain, and to estimate the potential impact of recombinant zoster vaccine (RZV) on avoided HZ cases and HZ-related pain prescriptions. This retrospective claims database study included patients from commercial, Medicare, and Medicaid plans between 2012 and 2017. Subjects with an HZ episode were assigned to three cohorts: "opioid", "non-opioid", and "no-treatment" cohorts. Subjects in the opioid cohort were matched to a non-HZ cohort. The potential impact of RZV vaccination on HZ case avoidance and resulting painkiller prescriptions was modeled. Over 25% of subjects with an HZ episode received opioids. Adjusted health-care costs were approximately double in the opioid cohort versus non-opioid or matched non-HZ cohorts. Postherpetic neuralgia, immunocompromised status, and comorbidities increased the risk for opioid prescription. RZV vaccination was predicted to avoid over 19, 000 patients from receiving opioid prescriptions for every 1 million adults aged ≥50 years. HZ-related prescriptions of opioids were common and led to increased health care costs. RZV vaccination may potentially reduce opioid prescriptions through decreasing HZ incidence. PLAIN LANGUAGE SUMMARY What is the context? Herpes zoster or shingles and its complications such as postherpetic neuralgia – a painful condition that affects the nerve fibers and skin – may lead to complex pain that can be addressed using opioids in some patients. The recombinant zoster vaccine (RZV) vaccine prevents shingles and, therefore, may reduce the use of opioids and the negative health outcomes and costs associated with it. What is new? In this retrospective medical claims study, including patients between 2012 and 2017, we evaluated the receipt of pain medication including opioids in herpes zoster patients, and assessed factors associated with opioid prescription. estimated health care resource utilization and costs associated with opioid use among patients with herpes zoster. assessed the impact of vaccination on opioid prescriptions. Among subjects receiving opioids, 78.5% started with a weak opioid dose. Dose escalation was uncommon. Postherpetic neuralgia, immunocompromised status, and comorbidities are the main risk factors associated with opioid prescription. Health care costs are almost double in patients with herpes zoster receiving opioids compared with patients without an opioid prescription. In a population of 1 million adults aged 50 years or older, vaccination with the recombinant zoster vaccine could prevent over 19, 000 patients from receiving opioids. What is the impact? Prevention of herpes zoster through vaccination may be a highly effective strategy to reduce opioid prescriptions and costs related to pain management in a susceptible population. Increasing RZV vaccination coverage in adults aged ≥50 years may further reduce potential opioid prescriptions through a decrease in shingles incidence.